Declining socioeconomic inequalities in hospital care use and case fatality rates for stroke and ischaemic heart disease in China during 2009–16: a prospective study of 0·5 million adults. Issue 1 (October 2019) - Levy, Muriel; Chen, Yiping; Clarke, Robert; Bennett, Derrick; Tan, Yunlong; Guo, Y; Bian, Zheng; Lv, Jun; Yu, Canqing; Li, Liming; Yip, Winnie; Chen, Zhengming; et al.
Abstract: Background: China initiated major health-care reforms in 2009 to provide health-care coverage for all by 2020. Little is known about their long-term effect on inequalities in health-care use and outcomes across socioeconomic groups. We aimed to examine trends in hospital care use and case fatality rates for stroke and ischaemic heart disease over 8 years during the implementation of the reforms, overall and by socioeconomic status. Methods: In this prospective study, we enrolled adults (30–79 years) from ten regions in China, with linkage to mortality and hospitalisation records. We used generalised linear models to estimate trends in annual hospitalisation rates, 28-day case fatality rates, and average length of stay for stroke, ischaemic heart disease, and any cause. Findings: During 2009–16, 794 824 hospital admissions (74 313 for stroke, 69 446 for ischaemic heart disease) were recorded among 505 995 participants. After adjustment for socioeconomic, lifestyle, and previous disease factors, hospitalisation rates increased by about 5% annually for stroke, ischaemic heart disease, and any cause. Higher socioeconomic groups had higher hospitalisation rates, but the annual increases were 2-fold higher in lower socioeconomic groups. Annual increases were higher in rural than urban areas (6·7% vs 3·7% for stroke; 10·0% vs 3·9% for ischaemic heart disease; both p<0·0001), in lower than higher education groups (9·0% vs 3·5% for stroke; 8·6% vs 3·3% for ischaemic heart disease; both p<0·0001), and in lower than higher income groups (8·5% vs 3·3% for stroke; 9·7% vs 5·3% for ischaemic heart disease; both p<0·0001). The annual increases in hospitalisation rates were higher for individuals in the rural or urban resident medical insurance scheme than for those enrolled in the urban employee scheme (6·1% vs 2·8% for stroke, 8·9% vs 3·5% for ischaemic heart disease; both p<0·0001). The case fatality rates for stroke and ischaemic heart disease were higher in lower socioeconomic groups, but differences decreased over time. Average length of stay decreased by about 2% annually for stroke, ischaemic heart disease, and any cause in all socioeconomic groups. Interpretation: Differences in hospital admission rates for stroke and ischaemic heart disease between socioeconomic groups have decreased since the initiation of health-care reforms in China in 2009, but additional strategies are needed to further reduce socioeconomic inequalities in health-care use and outcomes. Funding: Wellcome Trust, UK Medical Research Council, British Heart Foundation, Cancer Research UK, Kadoorie Charitable Foundation, China, Chinese Ministry of Science and Technology, and Chinese National Natural Science Foundation.